Microbiome Analysis Across a Natural Copper Gradient at a Proposed Northern Canadian Mine Site - Van Rossum, Thea; Pylatuk, Melanie M.; Osachoff, Heather L.; Griffiths, Emma J.; Lo, Raymond; Quach, May; Palmer, Richard; Lower, Nicola; Brinkman, Fiona S. L.; Kennedy, Christopher J. (Frontiers in Environmental Science, 2016)
Due to the environmental persistence, bioaccumulation, and toxicity of metals released by mining activities, mitigation methods are crucial to minimize impacts on aquatic environments. Bioremediation is one mitigation strategy used to reduce the potential for metal accumulation and toxicity in aquatic organisms. At a potential mine site in Yukon, Canada, elevated copper (Cu) concentrations and low pH are found in a water course near a naturally mineralized area; however, Cu concentrations and acidity are greatly reduced downstream. Physicochemical processes do not appear to explain this natural remediation and it is suggested that unique microbial communities may be responsible through Cu immobilization. To investigate the role of microbes in sequestering or transforming Cu in the water, biofilm samples were collected from 5 sites along a natural copper gradient: upstream of Cu introduction, on a Cu-rich tributary, 30 m downstream of Cu introduction where Cu levels were reduced, and 2 and 7 km further downstream where Cu concentrations were low. Taxonomic profiles of microbial communities (microbiomes) were compiled using DNA sequencing of 16S rRNA gene amplicons. Clear relationships between total Cu concentrations, pH and the microbiomes were evident. In the most Cu-affected samples, communities were dominated by bacteria from the Gallionellaceae family. Metagenomic sequencing profiled the genes present in microbiomes from the most Cu-contaminated sampling location and the area immediately upstream and showed that microbes in this area are well adapted to tolerate heavy metals. This study provides fundamental knowledge of microbial communities at a potential mine site and characterizes the genes likely involved in providing tolerance to an acidic and metals-rich environment. These results inform hypotheses for future experiments to support the development of bioremediation approaches that incorporate the use of native microorganisms at mining sites.